Intensitas Bermain Game Online dan Motivasi Belajar dengan Prestasi Belajar Mahasiswa Fakultas Kedokteran - Bio Lerianza; Deviani Utami; Supriyati Supriyati; Achmad Farich (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: The development of internet technology, including in Indonesia, is very rapid. One of the fastest-growing internet technologies is online gaming. Basically, students playing online games are only limited to entertainment for relieving tired after daily learning activities. Playing online games with high intensity can cause addiction or dependency continuously which will later influence the level of student concentration of learning. Purposes Knowing the relationship between the intensity of playing online games and learning motivation with learning achievement in the Students of the Faculty of General Medicine, University of Malahayati Force 2018. Methodology: The design of this study used an observational analytic approach with a cross-sectional design. The sampling technique in this study used a purposive sampling method and obtained a total sample of 118 people. Data analysis uses Spearman's correlation test. Result Spearman correlation bivariate statistical test results obtained each value of p-value = 0,000 in the intensity of playing online games and p-value = 0,000 in learning motivation. Conclusion: There is a significant relationship between the intensity of playing online games and learning motivation with learning achievement in the Students of the Faculty of General Medicine, University of Malahayati Force 2018